Paul and Asklepios: The Greco-Roman Quest for Healing and the Mission of Paul. (March 2019) - Stanley, Christopher D.
The apostle Paul says little in his letters about physical health or healing, whether for himself or his congregations. This is surprising in view of the vital importance of healing in other religious cults of the time and the gospels' depiction of Jesus as a healing deity. Sickness was endemic in Greco-Roman antiquity, and people sought cures from various types of practitioners who offered medical, religious and 'magical' modes of treatment. A number of explanations can be posited for Paul's relative silence about health and healing in his letters, but none is wholly convincing. The issues involved were so pressing that Paul must have addressed the topic in some form, even if it does not appear in his letters. His treatment of 'idol meat' in 1 Cor. 8 and 10 could provide an analogy for reconstructing what he might have said to his congregations on the subject.